Efisiensi Sling Bag Untuk Backpackers dari Segi Ergonomi dan Estetika yang Dipertimbangkan - Melan Maganti Farizi (PT. Pustaka Cendekia Publisher, 2025)
Backpackers are a term for people who like to travel far using only a backpack containing enough luggage. Not all backpackers can neatly organize the items they will take from their backpack directly, so an additional bag is needed such as a sling bag. Backpackers often move outdoors, so researchers must examine the aspects needed to make sling bag products more optimal, starting from aspects of comfort, aesthetics, and others. Researchers will use descriptive qualitative methods by interviewing, observing the product directly, and including quotes from experts. The results of this study obtained descriptive data findings about ergonomics, material, texture, color, accessibility in sling bag products.